A Primary Health Care-Anchored Migrant Right to Health: Insights from a Qualitative Study in Colombia - Stefano Angeleri (Health and Human Rights)
In recent years there has been a sustained rise in the number of international migrants, and scholarship and practice have increasingly focused on the relationship between health and migration. However, the entitlement to state-subsidized services for migrants with precarious or irregular legal status, often fleeing distressing living conditions, is typically limited to emergency lifesaving health treatment, with nonstate programs attempting to complement this constrained approach. This paper asks whether a primary health care (PHC) approach could serve as a blueprint for institutional priority-setting and for the realization of human rights obligations to help states meet their core international commitments regarding migrant health rights. I look at the multi-actor response in Colombia—where almost three million Venezuelans have sought to settle and many more have transited during the last nine years—as a case study to explore the possibility of a meaningful PHC-oriented right to health in the migration context. Using human rights law standards and commentaries, I suggest that, with some qualifications, this approach holds promise.